Ant type specimens (Hymenoptera, Formicidae) in the collection of Volodymyr Opanasovych Karawajew. Communication 2. Dolichoderinae - Radchenko, Alexander G.; Fisher, Brian L.; Esteves, Flavia A.; Martynova, Ekateryna V.; Bazhenova, Tatyana N.; Lasarenko, Svetlana N. (Zootaxa, 2024)
The article is the second in a series of catalogues of ant type specimens from the collection of V. O. Karawajew, stored at the Schmalhausen Institute of Zoology of the National Academy of Sciences of Ukraine (SIZK, Kiev). It includes data on 214 type specimens of 45 taxa of the subfamily Dolichoderinae, collected from around the world and described by V. O. Karawajew and other myrmecologists, which are currently assigned to 11 genera (Anonychomyrma, Azteca, Bothriomyrmex, Dolichoderus, Dorymyrmex, Iridomyrmex, Linepithema, Liometopum, Ochetellus, Tapinoma and Technomyrmex).